A three-dimensional analysis of morphological evolution and locomotor performance of the carnivoran forelimb. - Martín-Serra, Alberto; Figueirido-Castillo, Francisco Borja; Palmqvist-Barrena, Carlos Paul (PLOS, 2014)
In this study, three-dimensional landmark-based methods of geometric morphometrics are used for estimating the influence of phylogeny, allometry and locomotor performance on forelimb shape in living and extinct carnivorans (Mammalia, Carnivora). The main objective is to investigate morphological convergences towards similar locomotor strategies in the shape of the major forelimb bones. Results indicate that both size and phylogeny have strong effects on the anatomy of all forelimb bones. In contrast, bone shape does not correlate in the living taxa with maximum running speed or daily movement distance, two proxies closely related to locomotor performance. A phylomorphospace approach showed that shape variation in forelimb bones mainly relates to changes in bone robustness. This indicates the presence of biomechanical constraints resulting from opposite demands for energetic efficiency in locomotion –which would require a slender forelimb– and resistance to stress –which would be satisfied by a robust forelimb–. Thus, we interpret that the need of maintaining a trade-off between both functional demands would limit shape variability in forelimb bones. Given that different situations can lead to one or another morphological solution, depending on the specific ecology of taxa, the evolution of forelimb morphology represents a remarkable ‘‘one-to-many mapping’’ case between anatomy and ecology.
Keywords: Extremidades; Aparato locomotor; Forelimb; Geometric morphometrics; Carnivorans; Locomotion